PERSEPSI PELANGGAN CHOCOMORY PADA PRODUK TIRAMISUSU DI BANDUNG - Dominicus Rico Christa; Tatan Sukwika; Levyda Levyda; Iman Basriman (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study analyzes the purchasing decision model on the Chocomory product brand. The variables studied consisted of price perception, quality perception, service perception, brand image, brand preference, advertising perception and purchase decision. A total of 100 people who are consumers of Chocomory were involved in the study as respondents. SEM analysis was conducted to analyze the research model. The results show that price perception, quality perception and service perception have a positive effect on brand image. However, directly perceived price and perceived quality have no influence on purchasing decisions. Brand image is the most influential factor in purchasing decisions. In addition, brand preference and advertising perception were found to have a positive effect on purchasing decisions.